Upaya Mengoptimalkan Sistem Informasi Pemerintah Daerah - Gozi Apniwansyah; I Putu Widiantara; Mega Trishuta Pathiassana (Universitas Musamus, Merauke, Papua, 2022)
Development planning must be supported by decent information system and recently it was suggested to apply Sistem Informasi Perencanaan Daerah (SIPD) replacing the old one. However, it is unknown whether SIPD will perform well. This research aim to study the effort to optimize SIPD in Sumbawa District which showed from the implementation preparation and adjustment of SIPD in the level of village, subdistrict, and district. Role of SIPD to regional development planning itself is also assessed. The research method used here is documentation of related document, observation to the regional bureau, and interview to a number of informants that are related to SIPD. From this research, an effort to optimalize the implementation of SIPD have been done which shown from a number of planned and sustained socializations in the level of village, subdistric, and district. Based on this SIPD have been adjusted by giving honor and smartphone application in the level of village, subdistrict, and district. SIPD was found supporting the regional development planning because of its positive influence on the factors that support the regional development planning. Thus, effort to optimalize SIPD in Sumbawa District was done by considering the situation in that district.